S-BPM ONE - Running Processes 5th International Conference, S-BPM ONE 2013, Deggendorf, Germany, March 11-12, 2013. Proceedings - Fischer, Herbert; Schneeberger, Josef; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed proceedings of the 5th International Conference on Subject-Oriented Business Process Management, S-BPM ONE 2013, held in Deggendorf, Germany, in March 2013. The papers are organized in topical sections on running concepts; running business process management types; running applications; running ideas; running solutions; running projects.
Running concepts -- Running business process management types -- Running applications -- Running ideas -- Running solutions -- Running projects.
Keywords: Computer science; Software engineering; Information systems; Information Systems; Computer Science; Software Engineering; Management of Computing and Information Systems; Computer Appl. in Administrative Data Processing; Information Systems Applications (incl. Internet).